2022
DOI: 10.1177/00033197211073407
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hemodialysis Duration on Coronary Artery Calcification Among Hemodialysis Patients Who Underwent Percutaneous Coronary Intervention

Abstract: Our study aimed to evaluate the prevalence and impact of coronary artery calcification (CAC) on hemodialysis (HD) patients with coronary artery disease (CAD) who underwent percutaneous coronary intervention (PCI). We enrolled 211 HD patients who underwent PCI (men: n = 155, age: 71 ± 1 0 years). Severe CAC was defined as calcification with an arc of 360° on intravascular ultrasound. Multivariate analysis was performed to determine the predictors of severe CAC. The impact of severe CAC on target lesion revascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A recent OCT study demonstrated that the calcium arc, calcium length, and calcium volume index were larger in CN lesions than in non‐CN lesions in patients with acute coronary syndrome 11 . Moreover, HD duration has been associated with severe calcium burden 22 . Accordingly, we believe that HD duration is important in predicting the presence of CN before PCI.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A recent OCT study demonstrated that the calcium arc, calcium length, and calcium volume index were larger in CN lesions than in non‐CN lesions in patients with acute coronary syndrome 11 . Moreover, HD duration has been associated with severe calcium burden 22 . Accordingly, we believe that HD duration is important in predicting the presence of CN before PCI.…”
Section: Discussionmentioning
confidence: 80%
“…11 Moreover, HD duration has been associated with severe calcium burden. 22 Accordingly, we believe that HD duration is important in predicting the presence of CN before PCI. Our data also demonstrated that the lesion location differed between the CN and non-CN groups.…”
Section: Characteristics Of Cn In Hd Patientsmentioning
confidence: 97%